Public-Private Cooperation in the Eurasian Economic Union: Lessons for Belarus - Krivorotko, Yuri; Vysotskaya, Alla (Socialiniai tyrimai, 2015)
Key success factors of public-private cooperation management in the Eurasian Economic Union countries are revealed in the paper. Key success factors of public- private cooperation (PPC) have been structured as follows: legislative base and the regulatory environment, partner relationship, risk management. The paper concludes that full presence of key success factors of PPC may significantly improve its functioning and efficiency. The study provides a methodological base that underpins PPC management by emphasizing partner interaction and relevant procedures and structures. Recommendations for PPC development in Belarus on the basis of public- private management experiences in some post-Soviet countries are presented. The research methodology is based on the approaches of Rockart, Boynton, Zmud, Hardcastle, Edwards to key success factors of PPC, as well as on those proposed by Mouraviev, Kakabadse, Bazhenov from the Eurasian Economic Union, in empirical studies - opinion of experts, PPC project managers survey. Statistical data from official sources, the State Statistics Committee, Ministry of Economics, public private partnership centers in Kazakhstan, Russia and Belarus, databases, etc. were also used.